"It's like a safety net for when things go wrong": key stakeholder and program user perspectives on a peer-led safe space program in Sydney, Australia - Phillip Wadds; Christopher M. Doran; Anthony Shakeshaft; Dam Anh Tran (BMC, 2023)
Abstract Background Safe Spaces are a harm reduction approach commonly utilised in nightlife and festival settings to address alcohol and other drug-related harms. Despite increasing use, there has been little independent evaluation of safe space programs. This study aimed to explore (1) program user satisfaction with and use of a safe space program implemented in Sydney, Australia (The Take Kare Safe Space (TKSS)), and (2) the strengths and weaknesses of TKSS from the perspective of key stakeholders. Methods Semi-structured, in-depth, interviews lasting between 30 min to 1 h were conducted with 38 key program stakeholders, including staff from police (n = 4), ambulance (n = 4), a local hospital accident and emergency room (n = 4), local council (n = 2), city 'rangers' (n = 2), the TKSS program (n = 4), licensed venues and other nightlife service providers (n = 4), and program users (n = 14). Purposive sampling was used to identify key stakeholders to participate in interviews. Results Stakeholders stated that the TKSS program had a number of core benefits, including that it filled a service gap in nightlife settings; improved the efficiency and effectiveness of emergency services and other stakeholders operating in nightlife precincts; provided welfare services through proactive and non-judgmental interventions; and facilitated a means to de-escalate conflict without engaging police. Perceived weaknesses of the program included a lack of public awareness about the program; staff and volunteer levels; and misunderstandings regarding the scope and function of the TKSS program by some stakeholders. Conclusion This study demonstrates the complex relationships that exist around the delivery of harm reduction in nightlife settings. In particular, it highlights the relative lack of servicing of public nightlife settings and the value of safe spaces/peer-to-peer safety ambassador programs in linking up care and filling this service gap. Further, it documents the extended benefit across key stakeholder groups of delivering proactive and non-judgemental harm reduction services and, in doing so, provides critical evidence around their efficacy in reducing AOD-related harms in the night-time economy.